Infective endocarditis following coil occlusion of perimembranous ventricular septal defect with the Nit-Occlud (®) Le device - Amal M El-Sisi; Yasser M Menaissy; Samia A Bekheet (Wolters Kluwer Medknow Publications, 2016)
The Nitinol coil system was recently developed by "PFM" specifically for the transcatheter occlusion of ventricular septal defects (VSD). The device consists of a coil fitted with polyester fibers designated for the closure of perimembranous defects with an aneurysmal septum and some muscular VSDs. We report a case of fatal acute infective endocarditis 10 days following the procedure.